2013
DOI: 10.2478/s13380-013-0116-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive brain stimulation in children: Applications and future directions

Abstract: Transcranial magnetic stimulation (TMS) is a neurostimulation and neuromodulation technique that has provided over two decades of data in focal, non-invasive brain stimulation based on the principles of electromagnetic induction. Its minimal risk, excellent tolerability and increasingly sophisticated ability to interrogate neurophysiology and plasticity make it an enviable technology for use in pediatric research with future extension into therapeutic trials. While adult trials show promise in using TMS as a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 148 publications
3
73
0
Order By: Relevance
“…Reviews on safety aspects of TMS in children suggest that harm to brain tissue from single or paired pulses is extremely unlikely (Gilbert et al, 2004; for review see Rajapakse and Kirton, 2013). Several authors have also highlighted the absence of reported adverse effects of TMS in children (Frye et al, 2008;Garvey and Mall, 2008;Quintana, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Reviews on safety aspects of TMS in children suggest that harm to brain tissue from single or paired pulses is extremely unlikely (Gilbert et al, 2004; for review see Rajapakse and Kirton, 2013). Several authors have also highlighted the absence of reported adverse effects of TMS in children (Frye et al, 2008;Garvey and Mall, 2008;Quintana, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…While human exposure to fields generated by different electromagnetic sources has raised a number of questions regarding potential adverse health effects, some biomedical applications of electromagnetic fields in medical diagnostic and for therapy purposes, such as TMS, recently become of particular importance [10], [32], [33], as evidenced by modeling efforts of several investigators [9], [10], [14], [34].…”
Section: B Exposure Scenario and Modelmentioning
confidence: 99%
“…Additionally to its employment in research, TMS has been examined in therapeutic trials as a treatment tool (Rajapakse and Kirton, 2013). In order to investigate complicated facets of the human brain as cognition or motor function, TMS has been popularly used (Fregni et al, 2006).…”
Section: Introductionmentioning
confidence: 99%